Korelasi Antara Zero Based Budgeting Dengan Efisiensi Operasional Pada Perusahaan Jasa Kontraktor - Rahmi Nadiar; Rahmatullah Alfikri; Annisa Tri Hidhayati; Fitra Izzadieny; Riyadatul Muthmainnah (AKUNTANSI 45, 2025)
This study aims to examine the correlation between the implementation of Zero-Based Budgeting (ZBB) and operational efficiency in contractor service companies. A quantitative method was used with a case study approach at CV. KMP. Data were collected through questionnaires using a Likert scale (1–4) involving 15 respondents, including project managers, budget staff, and field supervisors. The data analysis showed a Pearson correlation coefficient of 0.973 and a significance value of 0.000, indicating a positive and significant relationship between ZBB and operational efficiency. The application of ZBB has proven effective in reducing cost waste and enhancing project execution efficiency. This research contributes to the development of performance-based budgeting strategies to improve operational efficiency in contractor companies.